2018
DOI: 10.2478/bjdm-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Oral alterations in diabetes mellitus

Abstract: SummaryDiabetes mellitus is one of the most common chronic diseases which continue to increase in number and significance. It presents the third most prevalent condition among medically compromised patients referring for dental treatment. Diabetes mellitus has been defined as a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Hyperglycemia leads to widespread multisystem damage which has an effect on oral tissue. The present articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 74 publications
1
31
0
7
Order By: Relevance
“…People with diabetes experience salivary dysfunction, which can lead to decreased salivary flow and change in saliva composition. The estimated universal prevalence of xerostomia among diabetic patients ranges between 34% and 51%[1,2]. Xerostomia can lead to numerous problems such as difficulty in eating, swallowing, and speaking.…”
Section: Xerostomiamentioning
confidence: 99%
See 4 more Smart Citations
“…People with diabetes experience salivary dysfunction, which can lead to decreased salivary flow and change in saliva composition. The estimated universal prevalence of xerostomia among diabetic patients ranges between 34% and 51%[1,2]. Xerostomia can lead to numerous problems such as difficulty in eating, swallowing, and speaking.…”
Section: Xerostomiamentioning
confidence: 99%
“…Reduced cleansing and buffering capacity of the saliva, increase of carbohydrate in the saliva, and increased level of oral yeasts, mutans streptococci and lactobacilli can lead to an increase in the incidence of tooth decay. In addition, chronic hyperglycemia may cause irreversible pulpitis leading to pulp necrosis[1,2,5,7,8]. Some studies have shown that apical periodon-titis and radiolucent periapical lesions are more common in diabetic compared to nondiabetic individuals[1,5,9].…”
Section: Dental Cariesmentioning
confidence: 99%
See 3 more Smart Citations